Mycobacterium bovis Bacillus Calmette–Guérin Alters Melanoma Microenvironment Favoring Antitumor T Cell Responses and Improving M2 Macrophage Function - Lardone, Ricardo D.; Chan, Alfred A.; Lee, Agnes F.; Foshag, Leland J.; Faries, Mark B.; Sieling, Peter A.; Lee, Delphine J. (Frontiers in Immunology, 2017)
Intralesional (IL) Mycobacterium bovis Bacillus Calmette-Guérin (BCG) has long been a relatively inexpensive therapy for inoperable cutaneous metastatic melanoma (CMM), although IL-BCG skin mechanisms remain understudied. We analyzed IL-BCG-treated CMM lesions combined with in vitro studies to further investigate BCG-altered pathways. Since macrophages play a pivotal role against both cancer and mycobacterial infections, we hypothesized BCG regulates macrophages to promote antitumor immunity. Tumor-associated macrophages (M2) infiltrate melanomas and impair antitumor immunity. BCG-treated, in vitro-polarized M2 (M2-BCG) showed transcriptional changes involving inflammation, immune cell recruitment, cross-talk and activation pathways. Mechanistic network analysis indicated M2-BCG potential to improve IFN-γ responses. Accordingly, frequency of IFN-γ-producing CD4+ T cells responding to M2-BCG vs. mock-treated M2 increased (p<0.05). Moreover, conditioned media from M2-BCG vs. M2 elevated the frequency of granzyme B-producing CD8+ tumor-infiltrating lymphocytes (TIL) facing autologous melanoma cell lines (p<0.01). Furthermore, transcriptome analysis of IL-BCG-injected CMM relative to uninjected lesions showed immune function prevalence, with the most enriched pathways representing T cell activation mechanisms. In vitro-infected MM-derived cell lines stimulated higher frequency of IFN-γ-producing TIL from the same melanoma (p<0.05). Our data suggests BCG favors antitumor responses in CMM through direct/indirect effects on tumor microenvironment cell types including macrophages, T cells and tumor itself.